Correlation between intradialytic blood pressure variability and cognitive impairment in patients on maintenance hemodialysis - Jingfang Wan; Jun Liu; Jing Pan; Lili Fu; Dandan He; Yaru Yao; Yani He; Kehong Chen (BMC Nephrology)
Abstract Background The relationship between intradialytic blood pressure variability (BPV) and mild cognitive impairment (MCI) in maintenance hemodialysis (MHD) patients is currently unclear. Our present study aimed to illustrate the correlation between intra-dialysis BPV and CI in MHD patients. Methods Intradialytic SBP within 3 months before cognitive assessment of the patients were collected as baseline data and averaged as final data. The intradialytic SBP was converted to the following 4 candidate short-term BPV indices: standard deviation (SD), coefficient of variation (CV), average real variability (ARV), RANGE. Overall cognitive function was assessed by the Montreal Cognitive Assessment (MoCA) scale. Results The study finally enrolled 170 patients with 6662 dialysis records and 26,580 SBP measurements. The mean age of the patients was 57.99 years, the MCI prevalence was 78.24%. Intradialytic SBP ARV (average real variability) was notably higher in patients with MCI than in the non-MCI (NMCI) group (8.91 vs. 7.60, P = 0.042), but there was no statistical difference in the mean SBP and other BPV indices between the two groups. There was a non-linear relationship between SBP ARV and MCI, and the inflection point of SBP ARV was 7.52. Conclusion Our study found that high SBP ARV was closely associated with MCI, indicating that high SBP ARV may act as an indicator of MCI in MHD patients.